Dioscorea Zingiberensis New Saponin Inhibits the Growth of Hepatocellular Carcinoma by Suppressing the Expression of Long Non-coding RNA TCONS-00026762 - Liu, Xing; Zhou, Pingsheng; He, Keqing; Wen, Zhili; Gao, Yong (Frontiers in Pharmacology, 2021)
Background: The etiology and carcinogenesis of hepatocellular carcinoma (HCC) are associated with various risk factors. Saponins extracted from Dioscorea zingiberensis C. H. Wright exhibit antitumor activity against HCC. This study aimed to investigate the effect and the underlying mechanism of Dioscorea Zingiberensis new saponin (ZnS) on HCC. Methods: Human HCC cell lines, Huh7 and SMMC-7721, were treated with different concentrations of ZnS. Cell apoptosis was determined via flow cytometry assay. Differentially expressed lncRNAs (DElncRNAs) in ZnS-treated SMMC-7721 cells were determined through RNA-sequence. The role of lncRNA TCONS-00026762 in HCC was investigated gain of function analysis, along with cell proliferation, apoptosis, and invasion in HCC cells. A subcutaneous xenograft of SMMC-7721 cell lines was established to study the effects of TCONS-00026762 in vivo. The expression of apoptosis-related proteins was detected in vivo and in vitro via western blotting. Results: ZnS inhibited the proliferation of HCC cell in a dose-dependent manner. ZnS could induce apoptosis in HCC cells. Illumina sequencing results showed that 493 DElncRNAs were identified in ZnS-treated SMMC-7721 cells. TCONS-00026762 expression was down-regulated in the ZnS-treated SMMC-7721 cells. TCONS-00026762 inhibited the effect of ZnS on the proliferation, apoptosis, and invasion of HCC cells. ZnS inhibited the tumor growth, while, TCONS-00026762 promoted tumor growth in vivo. Furthermore, ZnS and TCONS-00026762 regulated cell apoptotic pathways. Conclusions: ZnS significantly inhibits the viability, apoptosis, invasion, and tumorigenicity of HCC cells by regulating the expression of TCONS-00026762. Our findings provide novel insights into the potential role of lncRNA in HCC therapy.